Metal-free catalyst, preparation method and application of metal-free catalyst in preparation of benzyl alcohol by transfer hydrogenation of biomass-based benzaldehyde
By developing metal-free nitrogen-doped carbon catalysts, the problem of low activity in existing catalysts in ethanol is solved, and efficient catalytic conversion of benzaldehyde to benzal alcohol is achieved, which improves the selectivity and stability of the catalyst while reducing costs.
Patent Information
- Application Number
- CN202411704098.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-04
AI Technical Summary
The catalysts used in the transfer and hydrogenation process of biomass-based benzaldehyde have problems such as acidic sites, large amount of metal elements and low activity in ethanol.
A metal-free catalyst was developed using nitrogen-doped carbon catalysts. In the structure, nitrogen is used as the basic site of Lewis and does not contain Lewis acidic and acidic sites. This catalyst is prepared by pyrolysis of structural regulators and ZIF materials, and can efficiently catalyze the transfer hydrogenation reaction of benzaldehyde in ethanol.
The efficient catalytic conversion of benzaldehyde to benzal alcohol in ethanol is achieved, which avoids the occurrence of side reactions, improves the selectivity and stability of the catalyst, and reduces costs.
Smart Images

Figure CN119549177A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metal-free catalyst, a preparation method and application thereof in preparing benzyl alcohol by transfer hydrogenation of biomass-based benzaldehyde, and belongs to the technical field of catalyst preparation and application. Background Art
[0002] Converting the most abundant and renewable biomass resources in nature into high-value-added fine chemicals is an important way to achieve sustainable development of the chemical industry and a hot topic in current scientific research in countries around the world. Biomass-based benzaldehyde is an unsaturated carbonyl compound and an important component of the entire biomass-based high-value-added fine chemical system. Its selective reduction product, benzyl alcohol, can be widely used in industries such as medicine, pesticides, food, spices and coatings. Therefore, the study of the selective reduction of benzaldehyde has great scientific significance and application value. As we all know, benzaldehyde molecules contain carbon-oxygen double bonds (C=O) and carbon-carbon double bonds (C=C). When C=O undergoes hydrogenation reduction reaction, side reactions such as hydrogenolysis, decarbonylation and acetalization may also occur. Therefore, it is crucial to develop a suitable catalytic method to ensure the preferential hydrogenation of C=O and avoid deep hydrogenation of C=C as much as possible for the selective reduction of benzaldehyde to prepare benzyl alcohol.
[0003] At present, the selective reduction of benzaldehyde mainly includes traditional hydrogenation, electrochemical hydrogenation, photocatalytic hydrogenation, biocatalytic hydrogenation and MPV transfer hydrogenation. Among them, the MPV transfer hydrogenation does not require the use of exogenous hydrogen as a hydrogen donor, and has a very high specificity for the hydrogenation of C=O, which is very beneficial for the selective reduction of benzaldehyde. In the process of selectively reducing benzaldehyde using the MPV transfer hydrogenation method, the core work is to design a highly efficient and selective catalyst. Regarding the design of catalysts, the research focus in recent years has been mainly on some metal organic coordination polymer catalysts, such as Zr-DUT-69 (Catalysis Letters, 2019: 149: 1845-1855), Zr-PN (ACS Catalysis, 2016, 6: 7722-7727), Zr-TN (Green Chemistry, 2020, 22: 180-186), Zr-LS (Applied Catalysis B: Environmental, 2019, 248: 31-43), Zr-CA (Chemical Engineering Journal, 2018, 352: 110-119), Zr-DTMP (Journal of Energy Chemistry, 2019, 37: 82-92), Zr-ATMP (Molecular Catalysis, 2022, 524: 112253), Hf-GO (RSC Advances, 2020, 10:9985-9995), Hf-PDVP (Industrial Crops&
[0004] Products, 2022, 188:115606), Hf-MOF-808 (Molecular Catalysis, 2022, 522:112247), Hf-FDCA (Applied Catalysis B: Environment, 2018, l 227:79-89), Hf@CCSO3H (Catalysis Letters, 2020, 150:2038-2044) and Hf-DTMP (Sustainable Energy Fuels, 2019, 3:1033), etc.
[0005] It should be noted that although metal organic coordination polymer catalysts can effectively catalyze the selective reduction of benzaldehyde to benzyl alcohol, these catalysts contain a certain amount of Acidic sites, and The presence of acidic sites can promote the occurrence of side reactions such as benzaldehyde acetalization, etherification and ring hydrogenation to a great extent, thereby reducing the yield and selectivity of benzyl alcohol. Moreover, the metal content in the metal organic coordination polymer catalyst is very high, and some even exceed 30%, which not only greatly increases the cost of the catalyst, but also greatly reduces the atomic utilization of the catalyst. In addition, the metal organic coordination polymer catalyst mostly uses secondary alcohols (such as isopropanol) as hydrogen donors, and the effect is extremely unsatisfactory in more cheap and easy-to-make primary alcohols (such as ethanol), which also greatly limits the green production and subsequent applications of benzyl alcohol. Summary of the invention
[0006] The catalyst used in the existing biomass-based benzaldehyde transfer hydrogenation process has The present invention provides a metal-free catalyst and a preparation method thereof, which does not contain Acidic site, N in the catalyst structure is a Lewis basic site, and it can efficiently catalyze the transfer hydrogenation of benzaldehyde into benzyl alcohol in ethanol.
[0007] The technical solution adopted by the present invention is:
[0008] A metal-free catalyst, the catalyst being a nitrogen-doped carbon catalyst; in the catalyst, nitrogen acts as a Lewis basic site and does not contain Lewis acidic sites and Acidic sites.
[0009] The method for preparing the metal-free catalyst is to add a structure regulator solution into a solution containing a zinc source and imidazole for reaction, and then stand, centrifuge, wash, and dry to obtain a modified ZIF material.
[0010] The modified ZIF material is then pyrolyzed in a nitrogen atmosphere to obtain a metal-free catalyst.
[0011] Preferably, the structure modifier is polyvinyl pyrrolidone, cetyltrimethylammonium bromide or Pluronic F127.
[0012] Preferably, the zinc source is one or both of zinc nitrate and zinc acetate;
[0013] The imidazole is one or both of 1-methylimidazole and 2-methylimidazole.
[0014] Preferably, the usage ratio of the structure regulator, the zinc source and the imidazole is (2-6) g: (30-60) mmol: (140-200) mmol.
[0015] Preferably, the reaction conditions are: room temperature, 1-24 hours; the standing conditions are: room temperature, 1-8 hours; the drying conditions are: 50-100°C, 3-15 hours;
[0016] The pyrolysis conditions are: 800-1100°C, heating rate 2-10°C / min, 1-6h.
[0017] The metal-free catalyst is used in the transfer hydrogenation of biomass-based benzaldehyde to prepare benzyl alcohol or in the hydrogenation of biomass carbonyl compounds as substrates to prepare products, wherein the biomass carbonyl compounds are furfural, 5-methylfurfural, 5-hydroxymethylfurfural, p-methylbenzaldehyde, p-hydroxymethylbenzaldehyde or methyl levulinate, and the products are furfuryl alcohol, 5-methylfurfuryl alcohol, 2,5-furan dimethanol, p-methylbenzyl alcohol, p-hydroxymethylbenzyl alcohol or γ-valerolactone.
[0018] Preferably, the application comprises the following steps: adding a metal-free catalyst, biomass-based benzaldehyde and an alcohol in-situ hydrogen donor into a reaction kettle, heating and stirring to prepare benzyl alcohol.
[0019] Preferably, the amount of biomass benzaldehyde used is 1-5wt% of the amount of the alcohol in-situ hydrogen donor used, and the amount of the metal-free catalyst used is 10-50wt% of the amount of the biomass benzaldehyde used;
[0020] The alcohol in-situ hydrogen donor is ethanol, n-propanol, isopropanol, n-butanol or sec-butanol;
[0021] The reaction temperature is 120-200°C and the reaction time is 1-12h.
[0022] A method for increasing the average pore size and nitrogen content of a metal-free catalyst. The metal-free catalyst preparation process is to first prepare a ZIF material, then pyrolyze it in a nitrogen atmosphere, and add a structure regulator during the preparation of the ZIF material; wherein the structure regulator is polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide or Pluronic F127.
[0023] The beneficial effects of the present invention are:
[0024] This method uses a structure regulator and ZIF material as a sacrificial template to prepare a metal-free nitrogen-doped carbon-based catalyst (MF-NC) through solvent thermal self-assembly and high-temperature pyrolysis. The preparation process is simple, the surface morphology is controllable, and the surface area is high. It only contains Lewis basic sites, and does not contain Lewis acidic sites and Acidic sites. MF-NC can use cheap and renewable bioethanol as an in-situ hydrogen donor and reaction solvent to efficiently and selectively convert benzaldehyde into benzyl alcohol through the MPV transfer hydrogenation reaction mediated by Lewis basic sites. In addition, MF-NC can also selectively convert other biomass carbonyl compounds such as furfural, 5-methylfurfural, 5-hydroxymethylfurfural, p-methylbenzaldehyde, p-hydroxymethylbenzaldehyde and methyl levulinate into corresponding high-value-added products through the MPV transfer hydrogenation reaction. The reaction system is green and safe, the target product selectivity is high, and it has excellent catalytic stability and universality. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 SEM images of ZIF-8-F (a) and MF-NC-F (b) prepared in Example 1;
[0026] Figure 2 FT-IR image of MF-NC-F prepared in Example 1;
[0027] Figure 3 is the NH of MF-NC-F prepared in Example 1 3 -TPD graph;
[0028] Figure 4 is the XPS graph of MF-NC-F prepared in Example 1;
[0029] Figure 5 SEM images of ZIF-8-P (a) and MF-NC-P (b) prepared in Example 2;
[0030] Figure 6 SEM images of ZIF-8-C (a) and MF-NC-C (b) prepared in Example 3;
[0031] Figure 7 SEM images of ZIF-8 (a) and MF-NC-1 (b) prepared in Comparative Example 3;
[0032] Figure 8 This is the GC chromatogram of the preparation of benzyl alcohol by transfer hydrogenation of benzaldehyde catalyzed by MF-NC-F in Example 5. DETAILED DESCRIPTION
[0033] In this application, a metal-free nitrogen-doped carbon-based catalyst (MF-NC) is prepared by solvent thermal self-assembly and high-temperature pyrolysis with the help of a structure regulator and ZIF-8 as a sacrificial template. During the solvent thermal self-assembly process, the coordination process and surface morphology of ZIF-8 are regulated by adding a structure regulator; during the high-temperature pyrolysis process, the presence of the structure regulator can not only promote the pyrolysis process of ZIF-8 and increase the average pore size of MF-NC, but also stabilize the nitrogen element and increase its content. In addition, MF-NC only introduces Lewis basic sites (N), and does not introduce Lewis acidic sites and More importantly, MF-NC can efficiently and selectively convert benzaldehyde into benzyl alcohol via the Lewis basic site-mediated MPV transfer hydrogenation reaction, using cheap and renewable bioethanol as an in-situ hydrogen donor and reaction solvent.
[0034] Example 1
[0035] 4 g Pluronic F127, 40 mmol zinc nitrate and 160 mmol 2-methylimidazole were added to 100 mL, 200 mL and 300 mL methanol, respectively, marked as solution A, solution B and solution C, and stirred under ultrasound assistance until completely dissolved; solution A was slowly added to solution B and stirred for 1 hour; the mixed solution of A and B was added dropwise to solution C, continued to stir for 20 hours, and then allowed to stand at room temperature for 4 hours; the white precipitate was centrifuged and washed 5 times with methanol and deionized water respectively; the washed white precipitate was placed in a vacuum drying oven for drying, and dried at 80°C for 12 hours to obtain ZIF-8-F( Figure 1 Subsequently, ZIF-8-F was placed in a tubular reactor and heated to 950°C at a rate of 5°C / min under a nitrogen atmosphere. After high-temperature pyrolysis for 2 h, ZIF-8-F-derived carbon nitride was obtained, which was abbreviated as MF-NC-F ( Figure 1 middle b area).
[0036] SEM analysis showed that after high-temperature pyrolysis, ZIF-8-F had been transformed into MF-NC-F, and the surface of MF-NC-F became rougher due to the removal of Zn, Pluronic F127 and small molecular pyrolysis products in ZIF-8-F. FT-IR( Figure 2 ) Characterization results show: 1238cm -1 、1597cm -1 and 3404cm -1 The peaks at and are respectively attributed to the stretching vibration peaks of CN bond, C=N and NH bond, which indicates that N has been successfully introduced into MF-NC-F as a Lewis basic site. 3 -TPD( Figure 3) Characterization results showed that MF-NC-F did not introduce obvious Lewis acid sites and In addition, BET, ICP-AES and XPS analysis showed that the specific surface area of MF-NC-F was 670 m 2 / g, the average pore size is 3.2nm, the content of Zn element is 0, and the content of N element is 12.1% ( Figure 4 ).
[0037] Next, 0.2 g of benzaldehyde, 0.1 g of MF-NC-F and 19.8 g of ethanol were added to the reactor, and the temperature was raised to 140°C at a stirring speed of 400 rpm. After 2 h of MPV transfer hydrogenation reaction, benzyl alcohol was obtained. According to gas chromatography, the conversion rate of benzaldehyde was 68.5%, and the yield and selectivity of benzyl alcohol were 60.6% and 88.6%, respectively.
[0038] Example 2
[0039] 4 g of polyvinyl pyrrolidone, 40 mmol of zinc nitrate and 160 mmol of 2-methylimidazole were added to 100 mL, 200 mL and 300 mL of methanol, respectively, marked as solution A, solution B and solution C, and stirred under ultrasound assistance until completely dissolved; solution A was slowly added to solution B and stirred for 1 hour; the mixed solution of A and B was added dropwise to solution C, and continued to stir for 20 hours, and then allowed to stand at room temperature for 4 hours; the white precipitate was centrifuged and washed 5 times with methanol and deionized water respectively; the washed white precipitate was placed in a vacuum drying oven for drying, and dried at 80°C for 12 hours to obtain ZIF-8-P( Figure 5 Subsequently, ZIF-8-P was placed in a tubular reactor and heated to 950°C at a rate of 5°C / min under a nitrogen atmosphere. After high-temperature pyrolysis for 2 h, ZIF-8-P-derived carbon nitride was obtained, which is abbreviated as MF-NC-P ( Figure 5 middle b area).
[0040] SEM and FT-IR analysis showed that after high-temperature pyrolysis, ZIF-8-P had been transformed into MF-NC-P. Moreover, the surface of MF-NC-P became rougher due to the removal of Zn, polyvinyl pyrrolidone and small molecular pyrolysis products in ZIF-8-P. In addition, BET, ICP-AES and XPS analysis showed that the specific surface area of MF-NC-P was 495 m 2 / g, the average pore diameter is 3.1nm, the content of Zn element is 0, and the content of N element is 11.3%.
[0041] Next, 0.2 g of benzaldehyde, 0.1 g of MF-NC-P and 19.8 g of ethanol were added to the reactor, and the temperature was raised to 140°C at a stirring speed of 400 rpm. After 2 h of MPV transfer hydrogenation reaction, benzyl alcohol was obtained. According to gas chromatography, the conversion rate of benzaldehyde was 60.8%, and the yield and selectivity of benzyl alcohol were 53.5% and 88.1%, respectively.
[0042] Example 3
[0043] 4 g of hexadecyltrimethylammonium bromide, 40 mmol of zinc nitrate and 160 mmol of 2-methylimidazole were added to 100 mL, 200 mL and 300 mL of methanol, respectively, marked as solution A, solution B and solution C, and stirred under ultrasound assistance until completely dissolved; solution A was slowly added to solution B and stirred for 1 hour; the mixed solution of A and B was added dropwise to solution C, and continued to stir for 20 hours, and then allowed to stand at room temperature for 4 hours; the white precipitate was centrifuged and washed 5 times with methanol and deionized water respectively; the washed white precipitate was placed in a vacuum drying oven for drying, and dried at 80°C for 12 hours to obtain ZIF-8-C( Figure 6 Subsequently, ZIF-8-C was placed in a tubular reactor and heated to 950°C at a rate of 5°C / min under a nitrogen atmosphere. After high-temperature pyrolysis for 2 h, ZIF-8-C-derived carbon nitride, abbreviated as MF-NC-C ( Figure 6 middle b area).
[0044] SEM and FT-IR analysis showed that after high-temperature pyrolysis, ZIF-8-C had been converted into MF-NC-C. Moreover, the surface of MF-NC-C became rougher due to the removal of Zn, hexadecyltrimethylammonium bromide and small molecular pyrolysis products in ZIF-8-C. In addition, BET, ICP-AES and XPS analysis showed that the specific surface area of MF-NC-C was 418 m 2 / g, the average pore diameter is 3.1nm, the content of Zn element is 0, and the content of N element is 10.5%.
[0045] Next, 0.2 g of benzaldehyde, 0.1 g of MF-NC-C and 19.8 g of ethanol were added to the reactor, and the temperature was raised to 140°C at a stirring speed of 400 rpm. After 2 h of MPV transfer hydrogenation reaction, benzyl alcohol was obtained. According to gas chromatography, the conversion rate of benzaldehyde was 55.5%, and the yield and selectivity of benzyl alcohol were 47.3% and 85.2%, respectively.
[0046] Comparative Example 1
[0047] 40mmol zinc nitrate and 32mmol terephthalic acid were added to 300mL dimethylformamide, marked as solution A and solution B respectively, and stirred under ultrasound assistance until completely dissolved; solution A was added dropwise to solution B, and continued to stir for 1h at room temperature, and then the mixture was transferred to a reactor, heated to 120℃ and allowed to react for 24h; the white precipitate was centrifuged and washed with dimethylformamide and deionized water for 5 times respectively; the washed white precipitate was placed in a vacuum drying oven for drying, and dried at 80℃ for 12h to obtain Zn-BDC. Subsequently, Zn-BDC was placed in a tubular reactor, heated to 950℃ at a rate of 5℃ / min under a nitrogen atmosphere, and pyrolyzed at high temperature for 2h to obtain Zn-BDC-derived carbon, abbreviated as MF-C.
[0048] SEM and FT-IR analysis showed that after high-temperature pyrolysis, Zn-BDC had been converted into MF-C, and the surface of MF-C became rough due to the removal of Zn and small molecular pyrolysis products in Zn-BDC. In addition, BET, ICP-AES and XPS analysis showed that the specific surface area of MF-C was 1252 m 2 / g, the average pore diameter is 2.3nm, the content of Zn element is 0, and the content of N element is 0.
[0049] Next, 0.2 g of benzaldehyde, 0.1 g of MF-C and 19.8 g of ethanol were added to the reactor, and the temperature was raised to 140°C at a stirring speed of 400 rpm. After 2 hours of MPV transfer hydrogenation reaction, benzyl alcohol was obtained. According to gas chromatography, the conversion rate of benzaldehyde was only 5.3%, and the yield and selectivity of benzyl alcohol were 0, respectively. This shows that although MF-C has an extremely high specific surface area, it cannot catalyze the conversion of benzaldehyde into benzyl alcohol in ethanol. In other words, MF-C without metals and N does not have MPV transfer hydrogenation activity.
[0050] Comparative Example 2
[0051] 0.2g benzaldehyde, 0.1g MF-C in Comparative Example 1 and 19.8g ethanol were added to a reactor, heated to 170°C at a stirring speed of 400rpm, and subjected to MPV transfer hydrogenation reaction for 3h to obtain benzyl alcohol. Detection by gas chromatography showed that the conversion rate of benzaldehyde was only 28.6%, and the yield and selectivity of benzyl alcohol were 0, respectively, which further indicated that MF-C without metal and N did not have MPV transfer hydrogenation activity.
[0052] Comparative Example 3
[0053] 40mmol zinc nitrate and 160mmol 2-methylimidazole were added to 300mL methanol, marked as solution A and solution B respectively, and stirred under ultrasound assistance until completely dissolved; solution A was added dropwise to solution B, and stirring was continued for 20h, and then allowed to stand at room temperature for 4h; the white precipitate was centrifuged and washed 5 times with methanol and deionized water respectively; the washed white precipitate was placed in a vacuum drying oven for drying, and dried at 80℃ for 12h to obtain ZIF-8( Figure 7 Subsequently, ZIF-8 was placed in a tubular reactor and heated to 950°C at a rate of 5°C / min under a nitrogen atmosphere. After high-temperature pyrolysis for 2 h, ZIF-8-derived carbon nitride was obtained, which was abbreviated as MF-NC-1 ( Figure 7 middle b area).
[0054] SEM and FT-IR analysis showed that after high-temperature pyrolysis, ZIF-8 had been transformed into MF-NC-1, and the surface of MF-NC-1 became rough due to the removal of Zn and small molecular pyrolysis products in ZIF-8. In addition, BET, ICP-AES and XPS analysis showed that the specific surface area of MF-NC-1 was 586 m 2 / g, the average pore diameter is 2.9nm, the content of Zn element is 0, and the content of N element is 9.4wt%.
[0055] Next, 0.2 g of benzaldehyde, 0.1 g of MF-NC-1 and 19.8 g of ethanol were added to the reactor, and the temperature was raised to 140 ° C at a stirring speed of 400 rpm. After 2 hours of MPV transfer hydrogenation reaction, benzyl alcohol was obtained. According to gas chromatography, the conversion rate of benzaldehyde was 35.2%, and the yield and selectivity of benzyl alcohol were 27.6% and 78.3%, respectively. This shows that: compared with MF-C, MF-NC-1 has a relatively low specific surface area, but it can catalyze the conversion of benzaldehyde to benzyl alcohol in ethanol. In other words, N as a Lewis basic site is the real active site for catalyzing the conversion of benzaldehyde to benzyl alcohol, and has good MPV transfer hydrogenation activity.
[0056] By comparing Examples 1-3 with Comparative Example 3, it can be seen that the addition of a structural regulator can not only adjust the coordination environment and coordination process of ZIF-8, change the main structure and surface morphology of ZIF-8, but also promote the pyrolysis process of ZIF-8, improve the average pore size of metal-free catalysts (MF-NC-P, MF-NC-C and MF-NC-F), and can better stabilize the nitrogen element to increase its content, thereby greatly improving the MPV transfer hydrogenation activity. In other words, the metal-free catalyst provided in the present application significantly improves the conversion rate of benzaldehyde, the yield and selectivity of benzyl alcohol. In addition, compared with Examples 2 and 3, the MF-NC-F in Example 1 has a higher specific surface area, average pore size and N element content, showing a better catalytic effect.
[0057] Example 4
[0058] 0.2g of benzaldehyde, 0.1g of MF-NC-F in Example 1 and 19.8g of ethanol were added to a reactor, heated to 160°C at a stirring speed of 400rpm, and subjected to MPV transfer hydrogenation reaction for 2h to obtain benzyl alcohol. According to gas chromatography, the conversion rate of benzaldehyde was 86.3%, and the yield and selectivity of benzyl alcohol were 81.9% and 94.8%, respectively, which shows that the catalytic activity of the catalyst can be further improved by optimizing the reaction conditions.
[0059] Example 5
[0060] 0.2g benzaldehyde, 0.1g MF-NC-F in Example 1 and 19.8g ethanol were added to the reactor, and the temperature was raised to 170°C at a stirring speed of 400rpm. After 3h of MPV transfer hydrogenation reaction, benzyl alcohol was obtained. The gas chromatograph showed that the conversion rate of benzaldehyde was 100%, and the yield and selectivity of benzyl alcohol were 98.3% ( Figure 8 More importantly, MF-NC-F was separated from the reaction solution, washed and dried, and then subjected to the next MPV transfer hydrogenation reaction under the above reaction conditions. The results showed that after MF-NC-F was recycled five times, the conversion rate of HMF and the yield of BHMF could still reach 99.1% and 96.2%, respectively, showing good catalytic stability.
[0061] In order to better highlight the effectiveness of MF-NC-F in Example 1, the catalytic effect of MF-NC-F on benzaldehyde was studied using n-propanol, isopropanol, n-butanol and sec-butanol as in situ hydrogen donors, wherein the catalytic reaction conditions were adaptively adjusted accordingly due to the applicable scope of the hydrogen donor itself, as shown in Examples 6-9.
[0062] Example 6
[0063] 0.2 g of benzaldehyde, 0.1 g of MF-NC-F in Example 1 and 19.8 g of n-propanol were added to a reactor, heated to 170° C. at a stirring speed of 400 rpm, and subjected to MPV transfer hydrogenation reaction for 5 hours to obtain benzyl alcohol. Detection by gas chromatography showed that the conversion rate of benzaldehyde was 100%, and the yield and selectivity of benzyl alcohol were 99.1% respectively.
[0064] Example 7
[0065] 0.2 g of benzaldehyde, 0.1 g of MF-NC-F in Example 1 and 19.8 g of isopropanol were added to a reactor, heated to 160° C. at a stirring speed of 400 rpm, and subjected to MPV transfer hydrogenation reaction for 3 hours to obtain benzyl alcohol. Detection by gas chromatography showed that the conversion rate of benzaldehyde was 100%, and the yield and selectivity of benzyl alcohol were 99.7% respectively.
[0066] Example 8
[0067] 0.2 g of benzaldehyde, 0.1 g of MF-NC-F in Example 1 and 19.8 g of n-butanol were added to a reactor, heated to 170° C. at a stirring speed of 400 rpm, and subjected to MPV transfer hydrogenation reaction for 6 hours to obtain benzyl alcohol. Detection by gas chromatography showed that the conversion rate of benzaldehyde was 100%, and the yield and selectivity of benzyl alcohol were 98.5% respectively.
[0068] Example 9
[0069] 0.2 g of benzaldehyde, 0.1 g of MF-NC-F in Example 1 and 19.8 g of sec-butyl alcohol were added to a reactor, heated to 160° C. at a stirring speed of 400 rpm, and subjected to MPV transfer hydrogenation reaction for 4 hours to obtain benzyl alcohol. Detection by gas chromatography showed that the conversion rate of benzaldehyde was 100%, and the yield and selectivity of benzyl alcohol were 95.3% respectively.
[0070] It can be seen from Examples 6-9 that MF-NC-F can efficiently catalyze benzaldehyde to produce benzyl alcohol through the MPV transfer hydrogenation process in different alcohols, demonstrating excellent universality as an alcohol hydrogen donor.
[0071] In order to further demonstrate the effectiveness of MF-NC-F in Example 1, the substrate universality of MF-NC-F was studied using biomass carbonyl compounds such as furfural, 5-methylfurfural, 5-hydroxymethylfurfural, p-methylbenzaldehyde, p-hydroxymethylbenzaldehyde and methyl levulinate as substrates. The catalytic reaction conditions were adaptively adjusted according to the applicable scope of the substrate itself. The specific results are shown in Examples 10-15.
[0072] Example 10
[0073] 0.2g furfural, 0.1g MF-NC-F in Example 1 and 19.8g ethanol were added to a reactor, heated to 180°C at a stirring speed of 400rpm, and subjected to MPV transfer hydrogenation reaction for 5h to obtain furfuryl alcohol. Detection by gas chromatography showed that the conversion rate of furfural was 100%, and the yield and selectivity of furfuryl alcohol were 96.1% respectively.
[0074] Embodiment 11
[0075] 0.2 g of 5-methylfurfural, 0.1 g of MF-NC-F in Example 1 and 19.8 g of ethanol were added to a reactor, heated to 170° C. at a stirring speed of 400 rpm, and subjected to MPV transfer hydrogenation reaction for 5 hours to obtain 5-methylfurfuryl alcohol. Detection by gas chromatography showed that the conversion rate of 5-methylfurfural was 100%, and the yield and selectivity of 5-methylfurfuryl alcohol were 96.8% respectively.
[0076] Example 12
[0077] 0.2 g of 5-hydroxymethylfurfural, 0.1 g of MF-NC-F in Example 1 and 19.8 g of ethanol were added to a reactor, heated to 180° C. at a stirring speed of 400 rpm, and subjected to MPV transfer hydrogenation reaction for 6 hours to obtain 2,5-furan dimethanol. Detection by gas chromatography showed that the conversion rate of 5-hydroxymethylfurfural was 100%, and the yield and selectivity of 2,5-furan dimethanol were 95.7% respectively.
[0078] Embodiment 13
[0079] 0.2 g of p-methylbenzaldehyde, 0.1 g of MF-NC-F in Example 1 and 19.8 g of ethanol were added to a reactor, and the temperature was raised to 170° C. at a stirring speed of 400 rpm. After 3 hours of MPV transfer hydrogenation reaction, p-methylbenzyl alcohol was obtained. Detection by gas chromatography showed that the conversion rate of p-methylbenzaldehyde was 100%, and the yield and selectivity of p-methylbenzyl alcohol were 99.4% respectively.
[0080] Embodiment 14
[0081] 0.2 g of p-hydroxymethylbenzaldehyde, 0.1 g of MF-NC-F in Example 1 and 19.8 g of ethanol were added to a reactor, heated to 180° C. at a stirring speed of 400 rpm, and subjected to MPV transfer hydrogenation reaction for 8 hours to obtain p-hydroxymethylbenzyl alcohol. Detection by gas chromatography showed that the conversion rate of p-hydroxymethylbenzaldehyde was 100%, and the yield and selectivity of p-hydroxymethylbenzyl alcohol were 96.2% respectively.
[0082] Embodiment 15
[0083] 0.2g of methyl levulinate, 0.1g of MF-NC-F in Example 1 and 19.8g of ethanol were added to a reactor, heated to 180°C at a stirring speed of 400rpm, and subjected to MPV transfer hydrogenation reaction for 7h to obtain γ-valerolactone. Detection by gas chromatography showed that the conversion rate of methyl levulinate was 100%, and the yield and selectivity of γ-valerolactone were 97.5% respectively.
[0084] It can be seen from Examples 10-15 that MF-NC-F can not only efficiently catalyze the selective conversion of benzaldehyde into benzyl alcohol in ethanol, but also effectively catalyze the conversion of biomass carbonyl compounds such as furfural, 5-methylfurfural, 5-hydroxymethylfurfural, p-methylbenzaldehyde, p-hydroxymethylbenzaldehyde and methyl levulinate into corresponding high value-added products, which further illustrates that MF-NC-F has excellent catalytic activity and substrate universality.
[0085] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.
Claims
1. A metal-free catalyst, characterized in that The catalyst is a nitrogen-doped carbon catalyst; In the catalyst, nitrogen acts as a Lewis basic site and does not contain Lewis acidic sites and Acidic sites.
2. The method for preparing a metal-free catalyst according to claim 1, characterized in that: The method comprises adding a structure regulator solution into a solution containing a zinc source and imidazole to react, and then standing, centrifuging, washing, and drying to obtain a modified ZIF material. The modified ZIF material is then pyrolyzed in a nitrogen atmosphere to obtain a metal-free catalyst.
3. The method for preparing a metal-free catalyst according to claim 2, characterized in that: The structure regulator is polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide or Pluronic F127.
4. The method for preparing a metal-free catalyst according to claim 2, characterized in that: The zinc source is one or both of zinc nitrate and zinc acetate; The imidazole is one or both of 1-methylimidazole and 2-methylimidazole.
5. The method for preparing a metal-free catalyst according to claim 2, characterized in that: The usage ratio of the structure regulator, the zinc source and the imidazole is (2-6) g: (30-60) mmol: (140-200) mmol.
6. The method for preparing a metal-free catalyst according to claim 2, characterized in that: The reaction conditions are: room temperature, 1-24h; static conditions: room temperature, 1-8h; drying conditions: 50-100℃, 3-15h; The pyrolysis conditions are: 800-1100°C, heating rate 2-10°C / min, 1-6h.
7. The use of the metal-free catalyst according to claim 1 in the preparation of benzyl alcohol by transfer hydrogenation of biomass-based benzaldehyde or in the preparation of products by hydrogenation of biomass carbonyl compounds as substrates, characterized in that: The biomass carbonyl compounds are furfural, 5-methylfurfural, 5-hydroxymethylfurfural, p-methylbenzaldehyde, p-hydroxymethylbenzaldehyde or methyl levulinate, and the products are furfuryl alcohol, 5-methylfurfuryl alcohol, 2,5-furan dimethanol, p-methylbenzyl alcohol, p-hydroxymethylbenzyl alcohol or γ-valerolactone.
8. The use according to claim 7, characterized in that: The application comprises the following steps: adding a metal-free catalyst, biomass-based benzaldehyde and an alcohol in-situ hydrogen donor into a reaction kettle, heating and stirring to prepare benzyl alcohol.
9. The use according to claim 8, characterized in that: The amount of biomass benzaldehyde used is 1-5wt% of the amount of the alcohol in-situ hydrogen donor used, and the amount of the metal-free catalyst used is 10-50wt% of the amount of the biomass benzaldehyde used; The alcohol in-situ hydrogen donor is ethanol, n-propanol, isopropanol, n-butanol or sec-butanol; The reaction temperature is 120-200°C and the reaction time is 1-12h.
10. A method for increasing the average pore size and nitrogen content of a metal-free catalyst, wherein the metal-free catalyst preparation process is to first prepare a ZIF material and then pyrolyze it under a nitrogen atmosphere, characterized in that: During the preparation of ZIF materials, a structural regulator was added; Wherein, the structure regulator is polyvinyl pyrrolidone, hexadecyl trimethyl ammonium bromide or Pluronic F127.